Catalytic Enantioselective Intramolecular Aza‐Diels–Alder Reactions1. Issue 22 (13th April 2015) - Min, Chang; Lin, Chih‐Tsung; Seidel, Daniel
Abstract A readily available chiral Brønsted acid was identified as an efficient catalyst for intramolecular Povarov reactions. Polycyclic amines containing three contiguous stereogenic centers were obtained with excellent stereocontrol in a single step from secondary anilines and aldehydes possessing a pendent dienophile. These transformations constitute the first examples of catalytic enantioselective intramolecular aza‐Diels–Alder reactions.